The Level Global Competitiveness and Personal Level Development of Aceh Handicraft Entrepreneurs - Afri Yordan; Ahmad Saleh Nasution; Nor Aishah Buang (Penerbit Kemala Indonesia, 2017)
The aim of this study was to examine the level of global competitiveness and personal development of handicraft entrepreneurs. Differences between the level of competitiveness and educational background, level of labour skills, type of product, market area and sale methods. The total of 155 participants handicraft have business minimum of three years. The data were collected by distributing a questioner which is divided into six part, entrepreneur profiles, business profiles, business support, business market, used of technology, innovation of product and personal entrepreneur development. Questionnaires and instrument was adapted from Nor Aishah (2009) will use to research. Six person already selected were interviewed to further explicate and support the phenomenon this research. This study also determines whether the level competitiveness and personal development have a positive relationship with entrepreneurs. Result of descriptive analysis found that the mean level of the handicrafts entrepreneur competitiveness at a moderately high (min 3.46). Pearson correlation analysis showed a positive correlation but moderate strong between the level of competitiveness and the level of personal development entrepreneurs handicraft with value (r=0.443). One-way ANOVA test results shown there are two significant difference between the level competitiveness with industry type [F (2,152) = 0.042, p